Enlarged Parietal Foramina: MR Imaging Features in the Fetus and Neonate - Fink, A.M.; Maixner, W. (American Journal of Neuroradiology, 2006)
Summary: Enlarged parietal foramina are believed to be benign and familial and due to a variable degree of defective intramembranous ossification of the parietal bones. We report 2 patients with this condition in whom fetal and neonatal MR imaging studies illustrate the antenatal and perinatal evolution of this condition and the associated persistence of a falcine sinus. We discuss its relationship to the spectrum of cephalocoeles.